BHISHMA SAHNI’S ART OF TRANSLATION: MULTICULTURAL DIALOGUE AND THE SEARCH FOR LITERARY BEAUTY - Dev, Ravi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Translation is a creative process, which does not only transfer words from languages, but also works to build bridges between cultures, emotions and ideologies. It is a cultural dialogue in which language is only the medium, while meaning, context and sensibility are its root. The tradition of translation in Hindi literature has been very rich, in which many writers have enriched Hindi literature by translating great works from different languages. Bhishma Sahni’s contribution in this tradition is unique. Bhishma Sahni was not only a novelist, storyteller and playwright, but he was also a careful translator, who introduced Indian readers to world literature, especially by translating Russian literature into Hindi. He did not consider translation as just a process of translation, but saw it as a deeply creative act, where the translator gives a new sensibility, a new form to the text. In particular, his translations of Leo Tolstoy, Maxim Gorky, and other Russian writers reflect his linguistic skills, cultural understanding, and excellence in expression. This article will critically examine the art of translation of Bhisham Sahni, in which his major translations will be studied, his translation vision, craft, style, and ideological aspect will be analyzed. Through this, an attempt will be made to understand why and how he holds a special place in Hindi translation literature.